2020
DOI: 10.1111/pops.12719
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Talented Migrants: Majority and Minority Perspectives

Abstract: Many countries seek to specifically attract talented migrants in order to match the needs of national economies. In addition to the well-known intergroup antagonism between natives and immigrants, such immigration policies targeting talented migrants imply differentiation within the immigrant group, using normative criteria to distinguish desirable and economically useful immigrants from undesirable ones. Based on European Social Survey data (Round 7, N = 9856) comprised of national citizens from six multinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In this latter case, anti-immigrant prejudice is interpreted as a strategy to maintain the privileges of the high-status ingroup and status quo (see Jetten, 2019). Yet, in general, highly skilled immigrants are preferred over lowerskilled immigrants (Valentino et al, 2019), especially by national majority groups (Gale & Staerklé, 2021).…”
Section: Individual or Collective Threat?mentioning
confidence: 99%
“…In this latter case, anti-immigrant prejudice is interpreted as a strategy to maintain the privileges of the high-status ingroup and status quo (see Jetten, 2019). Yet, in general, highly skilled immigrants are preferred over lowerskilled immigrants (Valentino et al, 2019), especially by national majority groups (Gale & Staerklé, 2021).…”
Section: Individual or Collective Threat?mentioning
confidence: 99%
“…Converging evidence has shown that devalued members who have been historically excluded and treated unfairly tend to trust society and its authorities less than valued group members who have been more readily welcomed and included (Smith, 2010; see also Urbanska et al, 2019). As compared to so-called "talented migrants" who are generally cherished by receiving countries (Gale & Staerklé, 2021), many refugees and migrants are overly exposed to cumulative and prolonged forms of marginalization and exclusion (Esses et al, 2017;Gonzales et al, 2013). These vulnerable categories often face additional stressors stemming from insecure legal status and fear of deportation (Martiniello & Rea, 2014;van Meeteren, 2014), stressors that were further exacerbated during the COVID-19 outbreak (United Nations, 2020;WHO, 2020).…”
Section: Two Stages Linking Legal Status To Social and Political Trustmentioning
confidence: 99%
“…This civic integration perspective is the foundation of an "individualized immigration policy" (Gale & Staerklé, 2021), which uses individual criteria to determine if a person is allowed to enter and reside in a given country. Reflecting principles of equity theory (Walster, Walster, & Berscheid, 1978), individualized immigration policies "reward" valued in dividual contributions and assets of immigrants by granting them entry into the host nation.…”
Section: Individual Justice-based Immigration Criteriamentioning
confidence: 99%